Discours du président : Splendeurs et misères de Clio - Savard, Pierre (Historical Papers / Communications historiques, 1981)
AbstractClio in Canada today has notable strengths and weaknesses. Historiography itself has been greatly enriched as younger historians using better methods have opened up many new frontiers in labour, urban, Northern, and women's history, among others. As well, historians have had an important part in the flowering in many disciplines over the past decade of ethnic, regional, and Canadian studies-all leading to a fuller understanding of our heritage and nation. The last twenty years have seen a great expansion, too, in the numbers of historians, not only in the colleges and universities, but also among archivists (normally first trained in history) and government researchers (especially at the Department of National Defence and Parks Canada). As it approaches its sixtieth anniversary with well over two thousand members, the Canadian Historical Association itself is very healthy, a leader among learned societies in Canada and a strong force uniting far-flung historians through its annual meeting, its publications, and its defence of historians' interests, as in our recent representations in Ottawa regarding Bill C-43.But all is not well among Clio's Canadian disciples. Historians of countries other than Canada and especially francophone Quebeckers are still very much underrepresented in the CHA, despite laudable attempts to make the association more appealing to them. Our profession is more deeply threatened by attempts by the media through television soap operas and historical novels to equate history with a romantic popularization of the past, at the possible expense of reflective contemplation based on careful research and analysis. And if nineteenth-century historians too often came to history after a full career in public life, which led to obvious biases in their writings, do we now not risk the opposite extreme? Too many historians today are cold analysts removed from the world on isolated campuses, writing only for each other in specialized journals quite divorced from contemporary society. The natural critical capacity of historians — their training to take no evidence or information at face value — is too often lost in the affairs of the world. Despite our differences of temperament, ideology, subject fields, ages, and languages, we as historians in Canada are united in the belief that the past has more to teach us than the present. The lessons so gleaned we must make a source of wisdom for our contemporaries.